SMALL RUMINANTS PRODUCTION PRACTICES IN UPLAND RANGES OF - Asad Ullah Hyder, Abdul Salam Lodhi*, Muhammad Yaqoob and K.Z. Gondal (Pakistan Veterinary Journal, 2002)
A survey was conducted during the year 1999-2000 involving 120 farmers on a pre-tested questionnaire out of which 32. 70 and 18 farmers were from nomads. transhumant and sedentary classes respectively. It revealed that mostly selection was done in the male animals based on breeding efficiency, pedigree and individual performance of the animal. Males were selected within flock or taken from other flocks without any costs for some period. Majority of the farmers (57%) had adopted nutritional supplementation practices. For this purpose, they purchased fodder and concentrates rations. Nomads for feeding their animals were depending on grazing only, while transhumant and sedentary people were also growing fodder on agricultural land. Out of 120 respondents, 24.17 percent reported that they pay for grazing in the form of animals and their products. In nomads, transhumantand sedentary average losses of the mean flock size were 37.40, 22.58 and 25.37 percent respectively. Overall average animal losses were 39.48 with the standard deviation of 32.82 animals, which was 26.68 percent of mean flock size.